1994
DOI: 10.1111/j.1574-695x.1994.tb00438.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of human mononuclear cell response byHelicobacter pylori: Effects on isolated monocytes and lymphocytes

Abstract: Helicobacter pylori colonization of the human gastric mucosa causes a long-term, not self-limiting inflammation, suggesting that the microbe has properties to protect itself against the host immune defence system. Recently we were able to demonstrate that H. pylori suppresses the in vitro proliferative response of human peripheral blood mononuclear cells to antigens as well as to mitogens without affecting cell viability. The purpose of this study was to clarify which cell subsets of mononuclear cells are infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated that H. pylori affects immune infiltration, mainly by impairing proliferation or promoting apoptosis in T-cells [65][66][67]. In addition, gastric epithelial cells constitutively express class II Major Histocompatibility Complex molecules and may display a role as secondary antigen-presenting cells; however, the VacA toxin can impair the presentation of the Major Histocompatibility Complex-antigen [68].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that H. pylori affects immune infiltration, mainly by impairing proliferation or promoting apoptosis in T-cells [65][66][67]. In addition, gastric epithelial cells constitutively express class II Major Histocompatibility Complex molecules and may display a role as secondary antigen-presenting cells; however, the VacA toxin can impair the presentation of the Major Histocompatibility Complex-antigen [68].…”
Section: Discussionmentioning
confidence: 99%